Unity on Palestine Without Arab Unity? US Policy and the Post-Maksoud Arab World - Khalil Mousa Marrar (Arab Studies Quarterly, 2017)
Taking off from Clovis Maksoud's idea about the centrality of the Palestinians to Arab unity, this article traces out the historic struggle between secular nationalism and Islamism throughout and after the Arab Spring-turned-Winter and the complex interactions with American foreign policy. The trajectory of Middle Eastern and North African countries and politicized identity within them are analyzed in relation to that unsettled context. The article concludes with an evaluation of the possibilities for moving beyond the violence and authoritarianism in the Arab world using the lessons imparted by Maksoud.